2008
DOI: 10.1016/j.bandl.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between semantic and referential aspects of anaphoric noun phrase resolution: Evidence from ERPs

Abstract: a b s t r a c tIn this event-related brain potential (ERP) study, we examined how semantic and referential aspects of anaphoric noun phrase resolution interact during discourse comprehension. We used a full factorial design that crossed referential ambiguity with semantic incoherence. Ambiguous anaphors elicited a sustained negative shift (Nref effect), and incoherent anaphors elicited an N400 effect. Simultaneously ambiguous and incoherent anaphors elicited an ERP pattern resembling that of the incoherent ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 58 publications
4
62
3
1
Order By: Relevance
“…Further research is needed to see if these alternative explanations of the Nref effect can be teased apart (see also Nieuwland and Berkum, 2008a, for discussion). However, the latter explanation is more consistent with the sustained nature of the Nref and with previous Nref findings (e.g., Nieuwland & Van Berkum, 2008b), and is also suggested by the current findings.…”
Section: Unknown Referents and The Nrefsupporting
confidence: 73%
See 1 more Smart Citation
“…Further research is needed to see if these alternative explanations of the Nref effect can be teased apart (see also Nieuwland and Berkum, 2008a, for discussion). However, the latter explanation is more consistent with the sustained nature of the Nref and with previous Nref findings (e.g., Nieuwland & Van Berkum, 2008b), and is also suggested by the current findings.…”
Section: Unknown Referents and The Nrefsupporting
confidence: 73%
“…The Nref effect reflects genuine ambiguity at the level that is most relevant to discourse comprehension, the situation model Nieuwland & Van Berkum, 2006, 2008bVan Berkum et al, 1999). Referring expressions such as noun phrase anaphora and pronouns only elicit Nref effects in the context of two antecedents that are equally plausible referents (Nieuwland & Van Berkum, 2006;Nieuwland 3 This P600 effect, however, had a different morphology and time course than those reported in the other studies, possibly because the correct referent was available in the sentence, and one must tread carefully in assuming similar processes underlying these effects.…”
mentioning
confidence: 99%
“…Because our language comprehension system has only limited processing capacity, participants' focus on reestablishing a coherent semantic interpretation may have diverted their attention from the 'smaller concern' of the syntactically problematic utterance (for a similar result, see Nieuwland & Van Berkum, 2008). This could be true especially in the absence of a grammaticality judgment task.…”
Section: Absence Of a P600 Effect For Grammatical Case Violationsmentioning
confidence: 77%
“…Researchers in this field have long assumed that semantic processing and syntactic processing are reliably indexed by the N400 and P600 ERP component, respectively (e.g., Friederici, 1995;Hagoort, 2003). However, recent research has shown that semantic anomalies sometimes elicit P600 effects instead of N400 modulations (e.g., Bourguignon, Drury, Valois, & Steinhauer, 2012;Hoeks, Stowe, & Doedens, 2004;Kim & Osterhout, 2005;Kuperberg, Kreher, Sitnikova, Caplan, & Holcomb, 2007;Nieuwland & Van Berkum, 2005;Nieuwland & Van Berkum, 2008;Van Herten, Kolk, & Chwilla, 2005; for review, see Brouwer, Fitz & Hoeks, 2012;Kuperberg, 2007). For example, the sentence ''The hearty meal was devouring'' is semantically anomalous because meals cannot devour, but this type of sentence elicits a P600 effect rather than the expected N400 effect (e.g., Kim & Osterhout, 2005).…”
Section: Implications For the Electrophysiology Of Languagementioning
confidence: 99%
“…These windows are suitable to examine modulations of P600 effects induced by pronoun gender mismatch as well as of the Nref, which are both relatively extended ERP effects (see Nieuwland & Van Berkum, 2006, 2008b. Note that the 1000-1200 and 1200-1400 ms time windows correspond with P600 time windows on the post-critical word and that we label the time windows with reference to the critical word.…”
Section: Discussionmentioning
confidence: 99%